HERD INSTINCT BIAS, EMOTIONAL BIASES, AND INFORMATION PROCESSING BIASES IN INVESTMENT DECISIONS - Rohmad Fuad Armansyah (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2022)
The evolution of information during the COVID-19 pandemic has altered how investors invest. Investments can be made easily on a variety of digital platforms that provide easy access to information in investment decisions. Information media is expanding to promote investment decision making, boosting the rise and development of investor financial behavior bias. This study attempts to fill a knowledge gap in behavioral finance by concentrating on behavioral biases such as Herd Instinct Bias, Emotional Biases, and Information Processing Biases in capital market investment decisions. PLS-SEM (Partial Least Square-Structural Equation Modeling) was used to evaluate the data of 205 Indonesian capital market investors who are members of securities companies. The data confirm that overconfidence, herding bias, confirmation bias, and recency bias influence investor investment decisions, whereas endowment bias had no effect on investment decisions.